The Impact of Digital Content Marketing on Brand Defence: The Mediating Role of Behavioural Engagement and Brand Attachment - Sakher Faisal Ahmad AlFraihat; Ahmad Mahmoud Ali; Gassan Hodaifa; Mahmoud Alghizzawi (Administrative Sciences)
Marketers are increasingly interested in digital content marketing (DCM) strategies that have the potential to enhance consumer behaviour. However, there is a dearth of academic research that delves into the impact of DCM on brand defence. This study aims to investigate the impact of DCM on brand defence through behavioural engagement and brand attachment (in a Jordanian fashion industry case study). The results demonstrate a notable benefit of the direct effect of DCM on behavioural engagement, brand attachment, and brand defence. DCM is the strongest determinant of brand defence, followed by behavioural engagement and brand attachment. Behavioural engagement exerts a substantial beneficial impact on brand attachment. The results of this research indicate that both behavioural engagement and brand attachment significantly influence brand defence. The mediation results indicate that brand attachment fails to mediate the positive impact of DCM on brand defence. Moreover, the study determines that behavioural engagement mediates the positive impact of DCM on brand defence. This study is of high importance for marketing strategies, emphasising the pivotal importance of DCM in developing effective marketing approaches.